Use of nanocellulose in meat products - Marchetti, Lucas (2021)
In healthier reformulated meat products throughout animal fat reduction or its replacement with emulsified oil, hydrocolloids have been extensively studied and used as stabilizers. Among them, vegetable and bacterial nanocellulose are available to be employed in meat products. Each one has similar but particular characteristics, as high water-binding and oil-binding capacities, crystallinity, and rheological properties, and could act as an emulsifying and stabilizing ingredient. Therefore, they must be studied and selected according to the necessities of the different reformulated matrixes to improve their characteristics. Several studies have evaluated the nanocellulose addition in meat products with different fat levels or pre-emulsified oil as emulsion stabilizer or fat-replacer. This review aims to discuss the main applications of nanocellulose types in healthier meat products.